2012
DOI: 10.1186/1756-3305-5-161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the hexose transporter gene in benznidazole resistant and susceptible populations of Trypanosoma cruzi

Abstract: BackgroundHexose transporters (HT) are membrane proteins involved in the uptake of energy-supplying glucose and other hexoses into the cell. Previous studies employing the Differential Display technique have shown that the transcription level of the HT gene from T. cruzi (TcrHT) is higher in an in vitro-induced benznidazole (BZ)-resistant population of the parasite (17 LER) than in its susceptible counterpart (17 WTS).MethodsIn the present study, TcrHT has been characterized in populations and strains of T. cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…Increased transcript abundance of 3-hydroxyisobutyryl-coenzyme a hydrolase-like protein in the early passages relative to the late is in consistency with the preparedness of the infection ready parasites to use beta-oxidation of fatty acids, as observed by others ( Alcolea et al, 2009 ) (Supplementary Data Sheet S4 ). As opposed to the earlier observations ( Moreno et al, 2014 ), level of tyrosine amino transferase presented a reverse trend, as it was slightly downregulated in the early passage, although protein expression may reveal different results as observed previously for Trypanosoma cruzi ( dos Santos et al, 2012 ). Purine acquisition and inter-conversion is an important determinant of environmental sensing and morphogenesis in Leishmania .…”
Section: Resultscontrasting
confidence: 99%
“…Increased transcript abundance of 3-hydroxyisobutyryl-coenzyme a hydrolase-like protein in the early passages relative to the late is in consistency with the preparedness of the infection ready parasites to use beta-oxidation of fatty acids, as observed by others ( Alcolea et al, 2009 ) (Supplementary Data Sheet S4 ). As opposed to the earlier observations ( Moreno et al, 2014 ), level of tyrosine amino transferase presented a reverse trend, as it was slightly downregulated in the early passage, although protein expression may reveal different results as observed previously for Trypanosoma cruzi ( dos Santos et al, 2012 ). Purine acquisition and inter-conversion is an important determinant of environmental sensing and morphogenesis in Leishmania .…”
Section: Resultscontrasting
confidence: 99%
“…Overexpression of enzymatic activity related to antioxidant response, like that of tryparedoxin peroxidase, ascorbate peroxidase, and iron-superoxide dismutase, has been detected in T. cruzi populations resistant to BZ (Nogueira et al, 2006(Nogueira et al, , 2009(Nogueira et al, , 2012. In addition, the hexose transporter activity was 40% lower in a BZ-resistant T. cruzi population than in the susceptible control (dos Santos et al, 2012). Differences in susceptibility to BZ and NFX between T. cruzi strains (Filardi and Brener, 1987;Toledo et al, 2004) and/or the genetic diversity of the host (Filardi and Brener, 1987) might explain, in part, the variations in the efficacies of antiparasitic drugs.…”
Section: Introductionmentioning
confidence: 96%
“…In a previous study, the transcript level of the HT gene was observed to be more highly expressed in the BZ-resistant T. cruzi population. However, the authors observed a 40% reduction in transporter activity in this population, suggesting the existence of a regulatory mechanism at the protein activity level [ 52 ].…”
Section: Discussionmentioning
confidence: 99%